2017
DOI: 10.4103/1735-1995.200278
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D on glycemic control and oxidative stress in type 2 diabetes mellitus

Abstract: Background:Vitamin D deficiency may play a key role in the development of impaired glucose tolerance, type 2 diabetes mellitus (T2DM), and metabolic syndrome. Several studies have shown that Vitamin D has an antioxidant property. We aimed to investigate 25-hydroxy Vitamin D (25[OH]D) levels in patients with T2DM and in nondiabetic healthy controls and to ascertain the impact of 25(OH)D levels on glycemic control and oxidative stress in T2DM patients.Materials and Methods:Thirty male patients with T2DM and twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 52 publications
6
39
1
Order By: Relevance
“…Studies on the effect of vitamin D supplements on oxidative stress have reported conflicting results. For example, in contrast to George et al, who found an increase in hepatic glutathione peroxidase gene expression in streptozotocininduced diabetic rats, 20 Bhat et al reported reduced activity of GSH-dependent enzymes, glutathione peroxidase, and glutathione reductase in rats with depleted vitamin D. 21 Similarly, despite the availability of research suggesting that vitamin D supplementation in human beings reduces oxidative stress in conditions such as type 2 diabetes, 16,22 polycystic ovary syndrome, 23 and non-alcoholic fatty liver disease, 24 as well as in asymptomatic individuals, 25 other studies have shown that oxidative stress was not improved in type 2 diabetes 26 or in gestational diabetes. 27 The current study also found that vitamin D supplementation did not reduce oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies on the effect of vitamin D supplements on oxidative stress have reported conflicting results. For example, in contrast to George et al, who found an increase in hepatic glutathione peroxidase gene expression in streptozotocininduced diabetic rats, 20 Bhat et al reported reduced activity of GSH-dependent enzymes, glutathione peroxidase, and glutathione reductase in rats with depleted vitamin D. 21 Similarly, despite the availability of research suggesting that vitamin D supplementation in human beings reduces oxidative stress in conditions such as type 2 diabetes, 16,22 polycystic ovary syndrome, 23 and non-alcoholic fatty liver disease, 24 as well as in asymptomatic individuals, 25 other studies have shown that oxidative stress was not improved in type 2 diabetes 26 or in gestational diabetes. 27 The current study also found that vitamin D supplementation did not reduce oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
“…In another study evaluating healthy adults, the total oxidant status and ischemia-modified albumin, a marker of protein oxidation, were increased while the total antioxidant status was decreased in the vitamin D deficiency group. 14 Vitamin D deficiency has also been associated with increased oxidative stress in type 2 diabetic rats, 15,16 nutritional rickets, 17 multiple sclerosis, 18 and in healthy children. 19 All these data are consistent with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another meta-analysis study conducted in the obese and overweight people, supplementation with vitamin D did not have a significant impact on changes in selected inflammatory biomarkers levels [14]. Recently, a number of clinical trials evaluating vitamin D administration on different populations have been performed to determine if circulating levels of inflammatory markers and biomarkers of oxidative stress are affected among diabetic patients [15][16][17][18]. However, the sample size of these trials was small, the quality of the studies was variable, and the results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous observational studies showed that 25(OH)D3 levels were lower in patients with T2DM than in non-diabetic patients, and there was an inverse association between 25(OH)D3 levels and glycemic control parameters and inflammatory mediator [4][5][6][7]26]. However, the findings of interventional studies regarding the effect of Vitamin D3 administration on the control of T2DM are controversial [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, particular attention has been focused on the relationship between Vitamin D deficiency and a wide array of diseases, including T2DM [4][5][6][7][8]. In addition to the Vitamin D effects on calcium (Ca) homeostasis and bone health, Vitamin D also mediates non-calcemic actions in different tissues through Vitamin D receptors (VDRs) [9,10].…”
Section: Introductionmentioning
confidence: 99%